HUKUM ADMINISTRASI NEGARA DALAM UPAYA PEMBERANTASAN KORUPSI DI SEKTOR PUBLIK: STUDI KASUS E-KTP - Jamilah, Jamilah; Adiyati, Noor; Sugiyarti, Anita (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
This article investigates state administrative law in eradicating corruption. Corruption has plagued Indonesia for a long time. Even after the 1998 reforms, the democratization process was unable to suppress the symptoms of corruption. This research seeks to answer the important question of how regulations and policies amidst widespread corruption have eroded public trust in various sectors of society. Analysis of media coverage and secondary data was carried out to highlight E-KTP corruption case studies based on three main approaches: legal, institutional, and political. The results of the analysis show the need for a more comprehensive approach to examining the root causes of large-scale corruption (grand corruption) including efforts and improvements to cure and reduce corruption cases in Indonesia.